Executive summary of 'The antecedents of strategic pricing and its effect on company performance in the case of industrial service firms'. Issue 5 (19th August 2014) - Beal, Brian; Martin, Charles; Fall, TansyMarie
<x content-type="archive" xml:space="preserve">Abstract</x>